If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -90x + -45 = 45x + 45 Reorder the terms: -45 + -90x = 45x + 45 Reorder the terms: -45 + -90x = 45 + 45x Solving -45 + -90x = 45 + 45x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45x' to each side of the equation. -45 + -90x + -45x = 45 + 45x + -45x Combine like terms: -90x + -45x = -135x -45 + -135x = 45 + 45x + -45x Combine like terms: 45x + -45x = 0 -45 + -135x = 45 + 0 -45 + -135x = 45 Add '45' to each side of the equation. -45 + 45 + -135x = 45 + 45 Combine like terms: -45 + 45 = 0 0 + -135x = 45 + 45 -135x = 45 + 45 Combine like terms: 45 + 45 = 90 -135x = 90 Divide each side by '-135'. x = -0.6666666667 Simplifying x = -0.6666666667
| 6=(170-50)/(20-x) | | -14x-5=65 | | 2=8-6 | | -24=2(n+3)-2(3-3n) | | -10x-2=38 | | 2x+80=250 | | -3(x-2)+3(1+2x)=0 | | -2(m+7)=-2 | | 2(3+3n)-2(1+2n)=4 | | 3(2x-8)-10=2(x+1) | | e^2x+7=11 | | -2(2+2n)+3(n-1)=-6 | | -28=2(1+3n)-(3-3n) | | -9x^3y+4x^3y+5xy= | | (4x-20)+(x+12)+(x+1)=59 | | 5=3(-1-x)+2(x+3) | | 6=-3(1+p)+2(3+2p) | | -11+8x=5x+40 | | 25/4-2 | | (-1y+5x)5= | | 16=2(n-3)+2(2n+2) | | -3(3+x)+2(3x+1)=2 | | -39=3(-3m-3)-m | | 2x+(48-9c)-c=-2 | | 3x+3(2x+3)=36 | | -16t^2+112t+288= | | 8x+3z=2+3y | | 33=-3(-2+3x) | | 2x-5y+32=-1 | | 2x(2+2)=3 | | 3(3n+2)=33 | | -36=3(3p-3) |